2002
DOI: 10.1046/j.1365-2796.2002.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apoE genotype on the hypolipidaemic response to pravastatin in an outpatient setting

Abstract: Abstract. Peñ a R, Lahoz C, Mostaza JM, Jiménez J, Subirats E, Pintó X, Taboada M, López-Pastor A, The RAP study group (Hospital Carlos III; Instituto de Salud Carlos III, Madrid; Hospital de Puigcerdá, Gerona; Hospital de Bellvitge, Barcelona; Centro de Salud de Fuencarral; Hospital La Paz, Madrid, Spain). Effect of apoE genotype on the hypolipidaemic response to pravastatin in an outpatient setting. J Intern Med 2002; 251: 518-525.Background. Considerable variability exists in the plasma lipid and lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 31 publications
0
25
1
Order By: Relevance
“…43 Furthermore, the average decrease in LDL-C in our study was about similar for cerivastatin-and atorvastatin-treated patients, À36 and À38%, respectivley, and À24% LDL-C response to pravastatin in our study matched results of a Spanish outpatient study with 20% LDL lowering. 44 We deliberately did not choose to introduce a dose equivalence factor for our analysis, as others have chosen, 45 but tested for such an interaction. Since a significant interaction between LDL response and statin agent was confirmed in our study, this confounding effect was accounted for in the multivariate analysis of CETP haplotypes and LDL response.…”
Section: Limitationsmentioning
confidence: 99%
“…43 Furthermore, the average decrease in LDL-C in our study was about similar for cerivastatin-and atorvastatin-treated patients, À36 and À38%, respectivley, and À24% LDL-C response to pravastatin in our study matched results of a Spanish outpatient study with 20% LDL lowering. 44 We deliberately did not choose to introduce a dose equivalence factor for our analysis, as others have chosen, 45 but tested for such an interaction. Since a significant interaction between LDL response and statin agent was confirmed in our study, this confounding effect was accounted for in the multivariate analysis of CETP haplotypes and LDL response.…”
Section: Limitationsmentioning
confidence: 99%
“…The consensus is that e4 carriers appear to have attenuated lipid-lowering response, and e2 carriers have enhanced response. 13,17,[58][59][60][61][62][63][64][65][66][67][68][69][70] Few studies have examined the effects of variations in genes encoding other apolipoproteins. There are reports that polymorphisms in APOB, the gene encoding the major structural protein in both LDL and triglyceride-rich lipoproteins, may alter LDLC response; whereas variation in the APOAI gene, encoding the major structural protein in HDL, may alter HDLC response.…”
mentioning
confidence: 99%
“…It is also possible that subjects with the å4 allele are treated differently because some studies reported that their lipid response to statins is less favourable compared to the other genotypes [10][11][12][13][14]. However, other studies did not find such differences [15][16][17][18]. A lack of statistical power may also explain why we did not find a difference in effectiveness of statins in individuals with and without the å4 allele.…”
Section: Discussionmentioning
confidence: 83%
“…While other studies could not confirm these findings [15][16][17][18], in a substudy of the Scandinavian Simvastatin Survival Study (4S), subjects with the å4 allele with a history of myocardial infarction or angina pectoris had an almost two-fold higher risk of dying in a follow-up period of approximately 5.5 years compared to patients without an å4 allele. The increased risk of death was not accompanied by an increased risk of a major coronary event.…”
Section: Introductionmentioning
confidence: 99%